The Effectiveness Of Productive Reading Technique For Non English Department Of STKIP PGRI Nganjuk - Caltira Rosiana (Dharma Pendidikan, 2019)
Most of the students form non English Department have difficulties to understand the scientific reading text and served it in verbal based on their understanding. Then, Productive Reading Technique is one of techniques that could improve the students’ critical thinking trough scientific reading text, especially for students’ non English Department. This is the way to prepare the students’ to achieve their understanding in scientific reading text in TOEFL test. This research designed in experimental way and served as control class and experiment class. Through this research, the students faced some activities that improved their reading skill. The result in pre-test is 54,24 and the students’’ post-test 73,9, even this research is not significant but Productive Reading Technique effective to solve the students’ problem for Non English Department.